ANALYSIS OF THE INFLUENCE OF THE RUPIAH'S EXCHANGE RATE ON THE AMERICAN DOLLAR ON THE INDONESIAN COMPOSITE INDEX - Hendro Widjanarko (Sean Institute, 2023)
This study aims to analyze the effect of exchange rates (exchange rates) on stock prices in several countries. The results of this study resulted in several different conclusions regarding the variables that previously influenced other variables. Based on this, research was carried out on the causal relationship between the exchange rate of the rupiah against the U.S. dollar and the ICC, which was intended to determine whether there was a relationship between the exchange rate variable and the Jakarta Composite Index (IHSG) in Indonesia as an object. Research and find out which variable first affects the change in a variable as a form of the pattern of causality relationship with the population for the variable. Granger Causality is the model used in this study, and it is intended because it is used to test cause-and-effect relationships or causality relationships in which the clarity of the relationship between variables is not yet known. But before entering the Granger Causality stage, a Unit Root Test (URT) test was carried out to determine the stationarity of the data. From the results of the Unit Root Test, it was found that the exchange rate variable, as well as the ICI, were stationary, so the next step was to carry out the Granger The causality test, which obtained the results, was also used as a conclusion that the exchange rate of the rupiah against the U.S. dollar first affected changes in the ICC.